Sexual Intimacy and the Cultural Learning Relation - Donovan Plumb (Adult Education Research Conference, 2007)
This paper reflects on what we can learn about adult learning by pondering the phenomenon of mature sexual intimacy. Deep learning transpires in this intersubjective context, the paper concludes, because sexual love opens us to deep felt vulnerabilities.